A Randomized Controlled Study to Evaluate the Role of Video-based Coaching in Training Laparoscopic Skills. Issue 5 (May 2015) - Singh, Pritam; Aggarwal, Rajesh; Tahir, Muaaz; Pucher, Philip H.; Darzi, Ara
Abstract : Objective: This study evaluates whether video-based coaching can enhance laparoscopic surgical skills performance. Background: Many professions utilize coaching to improve performance. The sports industry employs video analysis to maximize improvement from every performance. Methods: Laparoscopic novices were baseline tested and then trained on a validated virtual reality (VR) laparoscopic cholecystectomy (LC) curriculum. After competence, subjects were randomized on a 1:1 ratio and each performed 5 VRLCs. After each LC, intervention group subjects received video-based coaching by a surgeon, utilizing an adaptation of the GROW (Goals, Reality, Options, Wrap-up) coaching model. Control subjects viewed online surgical lectures. All subjects then performed 2 porcine LCs. Performance was assessed by blinded video review using validated global rating scales. Results: Twenty subjects were recruited. No significant differences were observed between groups in baseline performance and in VRLC1. For each subsequent repetition, intervention subjects significantly outperformed controls on all global rating scales. Interventions outperformed controls in porcine LC1 [Global Operative Assessment of Laparoscopic Skills: (20.5 vs 15.5; P = 0.011), Objective Structured Assessment of Technical Skills: (21.5vs 14.5; P = 0.001), and Operative Performance Rating System: (26 vs 19.5; P = 0.001)] and porcine LC2 [Global Operative Assessment of Laparoscopic Skills: (28 vs 17.5; P = 0.005), Objective Structured Assessment of Technical Skills: (30 vs 16.5; P < 0.001), and Operative Performance Rating System: (36 vs 21; P = 0.004)]. Intervention subjects took significantly longer than controls in porcine LC1 (2920 vs 2004 seconds; P = 0.009) and LC2 (2297 vs 1683; P = 0.003). Conclusions: Despite equivalent exposure to practical laparoscopic skills training, video-based coaching enhanced the quality of laparoscopic surgical performance on both VR and porcine LCs, although at the expense of increased time. Video-based coaching is a feasible method of maximizing performance enhancement from every clinical exposure. Abstract : Despite equivalent exposure to practical laparoscopic skills training, video-based coaching enhanced the quality of laparoscopic surgical performance on both virtual reality and porcine laparoscopic cholecystectomies. Enhanced quality came at the expense of increased time. Video-based coaching is a feasible method of maximizing performance enhancement from every clinical exposure.